2009
DOI: 10.1097/cej.0b013e3283240460
|View full text |Cite
|
Sign up to set email alerts
|

Impact of metabolic factors on subsequent cancer risk: results from a large-scale population-based cohort study in Japan

Abstract: The impact of metabolic factors, which are major risk factors for cardiovascular disease, on total cancer risk has not been clarified. We prospectively examined whether metabolic factors and their aggregates predict the subsequent occurrence of total and major sites of cancer in the Japan Public Health Center-based Prospective Study. A total of 27 724 participants (9548 men and 18 176 women) aged 40-69 years participating in a questionnaire and health checkup survey in 1993-1995 were followed for total cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
374
7
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(410 citation statements)
references
References 41 publications
25
374
7
4
Order By: Relevance
“…Nine studies were conducted in the USA (16,18,20,32,35,(37)(38)(39)(40) , one in Sweden (42) , five in Korea (6,9,10,22,27) , two in China (23,30) , eight in Japan (8,24,26,28,29,31,36,43) , one in Austria (41) and three in European countries (4,17,34) (Tables 1 and 2). Pooled analysis showed a significant association between serum TAG and CRN (n 29 studies; summary RR = 1·08; 95 % CI 1·05, 1·12, P < 0·00001; Fig.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Nine studies were conducted in the USA (16,18,20,32,35,(37)(38)(39)(40) , one in Sweden (42) , five in Korea (6,9,10,22,27) , two in China (23,30) , eight in Japan (8,24,26,28,29,31,36,43) , one in Austria (41) and three in European countries (4,17,34) (Tables 1 and 2). Pooled analysis showed a significant association between serum TAG and CRN (n 29 studies; summary RR = 1·08; 95 % CI 1·05, 1·12, P < 0·00001; Fig.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Some of the previous studies reported that diabetes was associated with increased risk of colon cancer but not rectal cancer in both men and women (Le Marchand et al 1997;Yang et al 2004). Other studies (Wideroff et al 1997;Inoue et al 2006;Limburg et al 2006) indicated that diabetes is positively associated with the development of colon cancer in men but not diabetic women, and that diabetes in both the sexes is not associated with the development of rectal cancer. The discrepancy across the results of these studies is probably due to different methodologies that were adopted, including dissimilarity in the baseline characteristics and ethnicities of the patients, in methods of outcome assessment, and duration of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is a discrepancy in the results reported for sex-and age-specific incidence and relative hazard ratio of colorectal cancer. Some of the previous studies have reported that both male and female diabetic patients are at high risk of developing colorectal cancer (Le Marchand et al 1997;Weiderpass et al 1997;Yang et al 2004), whereas some other studies have shown that the risk of developing colorectal cancer is high in either diabetic men alone (Adami et al 1991;Wideroff, L. et al 1997;Khaw et al 2004;Limburg et al 2006;Inoue et al 2006) or diabetic women alone (Nilsen and Vatten 2001). The inconsistency in age-and sex-specific results of previous studies may be attributable to dissimilarities in patient characteristics, care received by the study patients, and possibly, differential accuracy of diagnosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the Cancer Prevention Study II Nutrition Cohort, Campbell et al [8] found a moderate increase in risk of colorectal cancer among men with diabetes (pooled RR = 1.24; 95 % CI 1.08-1.44), but no such association among women. Inoue et al [9] using the Japan Public Health Center-Based Prospective Study, observed no increase in risk of colon cancer with diabetes after excluding cancer cases diagnosed within 5 years of diagnosis of diabetes (HR = 1.19, 95 % CI 0.91-1.55 for men and 1.14, 95 % CI 0.70-1.87 for women). Similarly, data from the Japan Collaborative Cohort (JACC) showed no statistically significant increased risk of colorectal cancer with diabetes (IRR = 1.37, 95 % CI 0.95-1.96) [10].…”
mentioning
confidence: 99%